Pelatihan Optimalisasi Konten Marketing menggunakan Aplikasi Artificial Intellegence (AI) bagi UMKM Kampoeng Batik Kauman Pekalongan - Ari Muhardono; Wenti Ayu Sunarjo; Daru Anggara Murty; Supajar Bayu Aji; Tri Lidia Sari (I-Com: Indonesian Community Journal, 2024)
Kampoeng Batik Kauman Pekalongan, a destination for shopping, cultural, and educational batik tourism in Pekalongan City, Central Java, faces significant challenges in promotion and competition with imitation products. This community service activity aims to enhance the promotional skills of batik SMEs through training in the use of artificial intelligence (AI) applications for marketing content creation. The training involved 18 participants from Kampoeng Batik Kauman SMEs and covered the use of AI applications such as ChatGPT, Gemini AI, Bing Image Creator, Canva AI, Photoroom AI, and Gamma AI to assist SMEs in generating ideas and creating engaging marketing content. Participant satisfaction data showed that 72.2% rated the training as very satisfactory, 24.5% as satisfactory, and 3.2% as moderately satisfactory. These findings demonstrate that AI-based marketing content training is highly beneficial for supporting the business promotion of Kampoeng Batik Kauman Pekalongan SMEs, particularly in marketing content creation.